Peran Gembala dalam Kepemimpinan Gereja Ekoteologis: Studi Biblikal Kritis terhadap Mandat Ciptaan - Yohanes Praprowarso; Yonathan Salmon Efrayim Ngesthi (Sekolah Tinggi Teologi Kanaan Nusantara, 2026)
The global ecological crisis, with its numerous natural disasters caused by human actions and policies, challenges the church to re-examine its theological role and responsibility towards God's creation. Church leadership, which has tended to be anthropocentric, has often failed to integrate the mandate of creation as an ethical and theological basis in pastoral practice. As a result, the role of the pastor as a spiritual leader has not been fully understood as that of a steward of creation who is ecologically responsible. The phenomenon of increasing discourse and practice of eco-theology in contemporary churches indicates a new awareness, but this has not been balanced with critical biblical reflection that places the pastor as the main actor of eco-theological leadership. This article aims to analyse the mandate of creation biblically and theologically and to formulate the role of the pastor as a church leader responsible for the sustainability of the relationship between God, humanity, and creation. It uses a qualitative method with a literature study and biblical analysis approach. It can be concluded that based on the mandate of creation, church leadership is understood biblically as an eco-theological calling that places the stewardship of creation as an integral part of pastoral responsibility. Pastors, in a biblical perspective, are positioned as leaders who integrate theology and pastoral praxis to guide the congregation in building right relationships with God, others, and nature. Thus, eco-theological church leadership has significant theological and pastoral implications for the contemporary church in responding to the environmental crisis in a faithful and responsible manner.AbstrakKrisis ekologis global dengan banyaknya bencana alam akibat ulah manusia dan kebijakannya menantang gereja untuk meninjau kembali peran dan tanggung jawab teologisnya terhadap ciptaan Tuhan. Kepemimpinan gereja yang selama ini cenderung berorientasi antroposentris sering kali belum mengintegrasikan mandat penciptaan sebagai dasar etis dan teologis dalam praksis penggembalaan. Akibatnya, peran gembala sebagai pemimpin rohani belum sepenuhnya dimaknai sebagai penatalayan ciptaan yang bertanggung jawab secara ekologis. Fenomena meningkatnya wacana dan praksis ekoteologi dalam gereja kontemporer menunjukkan adanya kesadaran baru, namun belum diimbangi dengan refleksi biblikal kritis yang menempatkan gembala sebagai aktor utama kepemimpinan ekoteologis. Artikel ini bertujuan menganalisis mandat penciptaan secara biblikal-teologis dan merumuskan peran gembala sebagai pemimpin gereja yang bertanggung jawab terhadap keberlanjutan relasi antara Allah, manusia, dan alam ciptaan. Menggunakan metode kualitatif dengan pendekatan studi literature dan analisis biblikal. Maka dapat disimpulkan bahwa berdasarkan mandat penciptaan, kepemimpinan gereja dipahami secara biblikal sebagai panggilan ekoteologis yang menempatkan pemeliharaan ciptaan sebagai bagian integral dari tanggung jawab pastoral. Gembala, dalam perspektif biblikal, diposisikan sebagai pemimpin yang mengintegrasikan teologi dan praksis pastoral untuk membimbing jemaat membangun relasi yang benar dengan Allah, sesama, dan alam. Dengan demikian, kepemimpinan gereja ekoteologis memiliki implikasi teologis dan pastoral yang signifikan bagi gereja kontemporer dalam merespons krisis lingkungan secara beriman dan bertanggung jawab.